Rainfall-Runoff Modeling in a Regional Watershed Using the MIKE 11-NAM Model - Saad, Alaa Hashim; Khayyun, Thair S. (Salehan Institute of Higher Education, 2024)
This study used the MIKE 11 NAM model to model stormwater runoff in a northern Iraqi regional watershed of the Greater Zab River. During model calibration (2003-2017), observed data on streamflow, evaporation, and rainfall were used to optimize the nine model parameters. In order to validate the model, independent data covering the years 2018 through 2022 was used. The model's efficacy was evaluated using statistical performance metrics, including the coefficient of determination (R2), Nash Sutcliffe efficiency coefficient (NSE), and Root Mean Square Error (RMSE). During calibration (NSE = 0.81, RMSE = 2.2, and R² = 0.82) and validation (NSE = 0.90, RMSE = 6.9, and R² = 0.93), the model's performance demonstrated good agreement between simulated runoff and observed. The good agreement was for the low stream flow values compared to the high ones, due to the low number of parameters, which makes it easier to calibrate. Often, hydrological models do not capture peak flow phenomena, but there is a tendency for a good estimate of the low and medium stream flow values. Approximately 69% of the nutrient flow into the basin originated from the catchment area, which lies inside Iraq, while the remaining 31% came from the Turkey watershed. Future hydrological modeling in the area at the watershed level can utilize this model. Doi: 10.28991/CEJ-2024-010-12-08 Full Text: PDF